Can AI Digital Personas for Well-Being Provide Social Support? A Mixed-Method Analysis of User Reviews - Radek Heissler; Juraj Jonáš; Nicole Carre; Karin Mostovoy; Eduardo L. Bunge (Human Behavior and Emerging Technologies)
Discussion: Overall, DPs were perceived positively by most reviews analyzed. Users reported that DPs provided emotional and companionship support, were helpful, and had anthropomorphic traits, but also had negative experiences with DPs and technical issues. The types of themes reported in the reviews predicted the user ratings.